The burden of adult asthma in Finland: impact of disease severity and eosinophil count on health care resource utilization - Viinanen A.; Lassenius M.I.; Toppila I.; Karlsson A.; Veijalainen L.; Idänpään-Heikkilä J.J.; Laitinen T. (TAYLOR & FRANCIS LTD, 2022)
Objective: To describe health care resource utilization (HCRU) and associated costs in adult patients referred for specialist asthma care in Southwest Finland, by disease severity and blood eosinophil count (BEC).
Methods: This non-interventional, retrospective registry study (GSK ID: HO-17-17558) utilized data from patients >18 years of age on the hospital register of the Hospital District of Southwest Finland. Data extraction was from January 1, 2004 to December 31, 2015; the index date was the first hospital visit within this period with an International Classification of Diseases-10 diagnosis code for asthma or acute severe asthma. Patients were categorized by asthma severity (based on medication use) and BEC (<300 or >= 300 cells/mu L). Total and asthma-related HCRU and estimated costs were recorded the year following index and for calendar years 2004-2015.
Results: Overall, 14,398 patients were included; 388 had severe asthma at index. BEC was available for 3781 patients; 1434 had a BEC >= 300 cells/mu L and 2347 had a BEC <300 cells/mu L. A total of 1241 patients had severe asthma; 270 patients had severe eosinophilic asthma (severe asthma and a BEC >= 300 cells/mu L). Patients with severe versus non-severe asthma had higher total- and asthma-related outpatient visits, inpatient days, emergency room visits and costs per patient year; those with BEC >= 300 cells/mu L versus
Conclusion: This study demonstrated a substantial burden associated with severe and/or eosinophilic asthma for adults in Finland.